If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 + 4(x + -4) = 13x + 2 + -9x Reorder the terms: -2 + 4(-4 + x) = 13x + 2 + -9x -2 + (-4 * 4 + x * 4) = 13x + 2 + -9x -2 + (-16 + 4x) = 13x + 2 + -9x Combine like terms: -2 + -16 = -18 -18 + 4x = 13x + 2 + -9x Reorder the terms: -18 + 4x = 2 + 13x + -9x Combine like terms: 13x + -9x = 4x -18 + 4x = 2 + 4x Add '-4x' to each side of the equation. -18 + 4x + -4x = 2 + 4x + -4x Combine like terms: 4x + -4x = 0 -18 + 0 = 2 + 4x + -4x -18 = 2 + 4x + -4x Combine like terms: 4x + -4x = 0 -18 = 2 + 0 -18 = 2 Solving -18 = 2 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| -(3z-4)=6z-3(3z+2) | | 0.8x-0.4(9-3x)=-0.2(x-4) | | 31-5(x+1)=x | | sqrt(x-2)=x-3 | | x+4y=-7 | | 4t/-9=-5 | | 5/54-2/24-3/96 | | x^2+4x=286 | | 5-2w/3=10 | | 2=12x^2+2x | | -16t^2+32t+256=0 | | x^2+15x=76 | | (2x-3)(3x+9)= | | 9(t-2)+3t=6(2t+4)-9 | | 2x=12x^2+2x | | 2x^3+20x^2+48=0 | | 7y+x=26 | | 16x-3+3x-5=-3x-63 | | 5(9x+4)=290 | | (300-x)100=110 | | 4(3n+4)=2(6n+8) | | y-9x=22 | | 8(10x-9)=488 | | X=11y-4 | | 12/36=4/c | | 0.85x+.05(10-x)=.10(-107) | | 11y-4=x | | 10/12=b/6 | | -4x(4x-1)=0 | | (-4.2x^4)(3x^7)= | | 7/y=49/98 | | 92-y=x |